Production of Single-Chain Variable-Fragments against Carbohydrate Antigens - Yoko Fujita-Yamaguchi (Antibodies, 2014)
The production of human single-chain variable-fragments (scFvs) against carbohydrate antigens by phage display technology is seemingly a logical strategy towards the development of antibody therapeutics, since carbohydrates are self-antigens. Panning and screening of phages displaying human scFvs using a variety of neoglycolipids presenting structurally-defined carbohydrates resulted in a number of candidate phage clones as judged by cautious evaluation of DNA sequences and specific binding to carbohydrate moieties of interest. ScFv proteins were expressed in prokaryotic or eukaryotic cells from the respective genes. The characterization of isolated scFvs gene products after establishing expression, production and purification of scFv protein in different expression systems demonstrated that the production of scFv-human IgG1 Fc conjugates were originally sufficient in the media of stably-transfected cells, but declined during early passages. Bacterial expression of soluble scFv proteins with binding activity suffered low yields, whereas overexpressed scFv proteins formed inclusion bodies, which required refolding. An insect cell expression system producing soluble and active scFv proteins was found to be cost- and time-effective. The best expression system and fine adjustments for the conditions to prepare active forms had to be determined for each scFv protein. The successful production of active scFv proteins seems to be dependent on their DNA and/or amino acid sequences.